RETRACTED: The economic case for blend fuels: A cost-benefit analysis in the European context - Cemil Koyunoğlu (Sustainable Technology and Entrepreneurship)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy).This article has been retracted at the request of the Editor-in-Chief.The journal was alerted to issues within this article including the presence of the phrase ''As of my knowledge cutoff in 2021,'' indicative of ChatGPT output, the unknown provenance of fourteen case studies, and a nonsensical Figure 1, as detailed here: https://pubpeer.com/publications/80DA33E23C3638EC6CDB6E0389C3B2.As per journal policy, the author was contacted and asked to provide an explanation to these concerns. The author failed to satisfactorily fulfil this request. It should be noted that upon submission, the author declared that Generative AI tools were used to write the manuscript. However, in the view of the journal their usage appears to have extended beyond improving language and readability and therefore represents a breach of journal policy.The Editor-in-Chief has lost confidence in the reliability of this article and has decided to retract it. The corresponding author, Dr Cemil Koyunoğlu, does not agree to the retraction. The journal sincerely regrets that these issues were not detected during the manuscript screening and evaluation process and apologies are offered to readers of the journal.